RUANG PUBLIK DAN RITUAL WARGA KAMPUNG KASEPUHAN CIPTAGELAR DI KABUPATEN SUKABUMI - Nuryanto, Nuryanto (-)
The space between building are meaning as areas opened can to accsess by the people, and usually be located between buildings. The space between building in this case, to be interesting because inside can to carried out of activity public characteristic in community scale limited. At first glance the space between building is a public space are property with communal by community or country facility in the interest of the space. But reality its not it. Some spaces between building is personal property. Fieldes the usually to purpose for sport, the majority is personal property and not yet to use and than to let use by the public and some times its make use of, untill definition of public space in this case not only the space for public society, but to carried out by self supporting people. This research are characteristic of eksploratif with use fenomenologic-hermenitic approach in the architecture and ethnografic. It can be concluded, the research shows that the fenomena of the space between building as the public space still to exploration as a general fenomena from the open space. The public space will be seen are meaning at the moment of ritual adat, like as: seren taun, ngadegkeun imah, hajat sasih, etc. In outside moments its, so the public space like as loosing clear function. The public space just to mean as the public space usual for the people activity every day. This research to give contribution for development research about of genius local and will be enrich instruction of vernacular architecture. In the praxiss, this research can to use in the design of public space Sundanese contemporer, like as: restaurant, , cafÃ©, etc.Â